Profiles of Learners of Turkish as a Second Language in Terms of Acculturation Orientation, Psychological Adjustment, and Perceived Cultural Distance - Nezir Temür; Gülnur Aydın (Sakarya University Journal of Education)
When individuals encounter a cultural circle other than the one that constructs their memory, self, and consciousness, they are likely to experience some adaptation problems. Especially for individuals living in a foreign country, such problems can be much more diverse. Therefore, it is extremely important to examine such problems by focusing on the individual’s perceptions and experiences in various dimensions. The aim of this study is to determine the profiles of learners of Turkish as a second language in terms of acculturation orientation, psychological adjustment, and perceived cultural distance and the relationship between them. In line with this aim, the correlational method, one of the quantitative research methods, was preferred in the study. The sample group consisted of 300 learners at B2, C1 and C1+ language levels who were studying at Turkish language teaching centres of different universities in Türkiye in the 2022-2023 academic year. A 7-point Likert-type short scale developed by Demes and Geeraert (2014) consisting of the dimensions of acculturation orientation, psychological adjustment, and cultural distance was used as a data collection tool; the data were analyzed using the SPSS 26.0 statistical package program. As a result of the research, it was found that the participants, who exhibited different profiles in terms of scores according to gender, language level, education level, reason for coming to Türkiye, native language, and number of languages known, showed that as their orientation toward home culture increased, their orientation toward Turkish culture and perceived cultural distance scores increased correlatively; however, their psychological adjustment scores decreased. While no relationship was found between the participants' orientation toward Turkish culture and their psychological adjustment and intercultural distance perceptions, it was observed that as their psychological adjustment scores increased, their perceived cultural distance scores decreased. Finally, the results obtained from the study were interpreted and discussed in the light of the literature. Various suggestions were also presented to the researchers by mentioning the limitations of the study.